1997
DOI: 10.1111/j.1432-2277.1997.tb00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of mucosal HPV DNA detection (types 6/11, 16/18, 31/35/51) in skin lesions of renal transplant patients

Abstract: Human papillomaviruses (HPV) probably play a role in the development of skin cancer in renal transplant recipients. Since some mucosal HPV are strongly related to cervical cancer, we compared the frequency of HPV DNA detection (mucosal types 6/1 I , 16/18, and 31/ 33/51) in skin cancer of renal transplant recipients (21 lesions) with that in normal subjects without immunodeficiency (21 lesions) and studied the frequency of these same HPV in benign lesions of renal transplant recipients (34 lesions) and normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…reported that, of the 18 cutaneous warts in transplant recipients, HPV 6/11 was detected in four of the samples (4/18, 36%). In another study, in 11 out of 34 (32.4%) benign lesions in renal transplant patients, cutaneous warts were positive for HPV DNA: eight common warts (three type 6/11, two type 16/18, one type 16/18 and 31/35/51, and two type 31/35/51) and three plantar warts (two type 16/18 and one type 31/35/51) . In the control group, three out of 30 (10%) benign lesions were positive: two common warts (one type 16/18 and one type 31/35/51) and one plantar wart (type 16/18).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…reported that, of the 18 cutaneous warts in transplant recipients, HPV 6/11 was detected in four of the samples (4/18, 36%). In another study, in 11 out of 34 (32.4%) benign lesions in renal transplant patients, cutaneous warts were positive for HPV DNA: eight common warts (three type 6/11, two type 16/18, one type 16/18 and 31/35/51, and two type 31/35/51) and three plantar warts (two type 16/18 and one type 31/35/51) . In the control group, three out of 30 (10%) benign lesions were positive: two common warts (one type 16/18 and one type 31/35/51) and one plantar wart (type 16/18).…”
Section: Discussionmentioning
confidence: 94%
“…Cutaneous HPV type 1 is frequently detected in plantar warts, and HPV 2, 4, 7 and 57 are reportedly found in common warts . Recently, there have been several reports on detection of mucosal HPV in skin lesions of transplant patients . Various hybridization techniques such as filter in situ hybridization, Southern blot hybridization, and polymerase chain reaction (PCR) were developed to detect HPV genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…They can occur on multiple localities and are mostly detected on sun‐exposed areas of skin. The identified mucosal viral types in warts of OTRs are HPV 1, 2, 3, 4 and 10, which are also detected in immunocompetent patients, and in addition low‐risk types HPV 6 and 11 and high‐risk types HPV 16, 18, 31, 35 and 51 6–9 …”
Section: Introductionmentioning
confidence: 99%